pYR4 From a Norwegian Isolate of Yersinia ruckeri Is a Putative Virulence Plasmid Encoding Both a Type IV Pilus and a Type IV Secretion System - Wrobel, Agnieszka; Ottoni, Claudio; Leo, Jack C.; Linke, Dirk (Frontiers in Cellular and Infection Microbiology, 2018)
Enteric redmouth disease caused by the pathogen Yersinia ruckeri is a significant problem for fish farming around the world. Despite its importance, only a few virulence factors of Y. ruckeri have been identified and studied in detail. Here, we report and analyze the complete DNA sequence of pYR4, a plasmid from a highly pathogenic Norwegian Y. ruckeri isolate, sequenced using PacBio SMRT technology. Like the well-known pYV plasmid of human pathogenic Yersiniae, pYR4 is a member of the IncFII family. 31% of the pYR4 sequence is unique compared to other Y. ruckeri plasmids. The unique regions contain, among others genes, a large number of mobile genetic elements and two partitioning systems. The G+C content of pYR4 is higher that of Y. ruckeri NVH_3758 genome, indicating its relatively recent horizontal acquisition. pYR4, as well as the related plasmid pYR3, comprise operons that encode for type IV pili and for a conjugation system (tra). In contrast to other Yersinia plasmids, pYR4 cannot be cured at elevated temperatures. Our study highlights the power of PacBio sequencing technology for identifying mis-assembled segments of genomic sequences. Comparative analysis of pYR4 and other Y. ruckeri plasmids and genomes, which were sequenced by the second and the third generation sequencing technology, showed errors in second generation sequencing assemblies. Specifically, in the Y. ruckeri 150 and Y. ruckeri ATCC29473 genome assemblies, we mapped the entire pYR3 plasmid sequence. Placing plasmid sequences on the chromosome can result in erroneous biological conclusions. Thus, PacBio sequencing or similar long-read methods should always be preferred for de novo genome sequencing. As the tra operons of pYR3, although misplaced on the chromosome during the genome assembly process, was demonstrated to have an effect on virulence, and type IV pili are virulence factors in many bacteria, we suggest that pYR4 directly contributes to Y. ruckeri virulence.